Recitation of Surah Al-Waqiah As The Cause of Rizqi - Mir’atun Nisa’ (Syntax Corporation, 2022)
Al-Qur'an Surah al-Waqiah textually contains the events of the Day of Judgment and a description of the state of heaven vs. hell. The description of heaven and hell is not only found in surah al-Waqiah but several verses in other surahs. Interestingly, Q.S. al-Waqiah in the community is known as the sura cause of fortune if read with specific provisions. This paper aims to look at the sources of the book of literature, which is the basis of the practice of reciting surah al-Waqiah as the cause of Rizqi. The theory used is the theory of the reception of the Koran. The method used is descriptive-analytical. The results of this library research are that Muslims have accepted the Q.S. al-Waqiah in an exegetical, aesthetic, and functional manner. Exegetically, surah al-Waqiah becomes a reading text; its meaning is interpreted in the books. Aesthetically, Surah al-Waqiah can also be read, sung beautifully, and functionally Surah al-Waqiah is read and written for Rizqi. From the search of the books, surah al-Waqiah, with its function as a cause for rizqi, comes from the hadith. Even though it is worth dhoif, but the hadith is classified as fadhail a'mal which by some scholars can be practiced in daily life.